Hotel Theming in China: A Qualitative Study of Practitioners' Views - Wassler, Philipp; Li, Xiang (Robert); Hung, Kam (Journal of travel & tourism marketing, 2015)
Facing increasing competition, many hotels have adopted "theming" as a marketing strategy. Although still in its fledgling stage, hotel theming has already gained popularity in the growing Chinese hotel market. This study conducted focus group discussions to understand the concepts behind hotel theming in China. Respondents were 41 practitioners from the Chinese hotel industry, who were enrolled in an executive graduate program. Data revealed that hotel theming has four analytical dimensions, namely, the current state, perceived facilitators, inhibitors, and future prospective for developing such strategy in China. Results showed that the specific traits of the Chinese hotel market are highly important for the success of hotel theming in the given context.